Tourists’ Characteristics, Travel Motivation and Satisfaction - Silva, Osvaldo Dias Lopes da (2020)
Our society is growing older and it is important to develop the senior tourism market. Consumers aged 55 and older are a fastest growing market segment and a major business opportunity. The purpose of this research is to develop and test a model to investigate the characteristics of the senior tourists that affect the factors of travel motivation and travel satisfaction. We intent to explore the existence of statistically significant differences in satisfaction between groups of senior tourists using the same categories. A path analysis is carried out in order to describe direct dependencies among a set of variables. In this study (n=537 senior tourists visiting the Azores islands) a model is proposed to identify the senior tourists’ characteristics which significantly affect each of the dependent variables (motivation factors and satisfaction) and which types of effects explain the association among variables. Travel satisfaction depends both on age group and perception of health status by the senior tourists. New opportunities can be found for both public and private sectors to develop and marketing new tourism products that can attract the right senior market segments.